The Effect of Learning Management System (LMS) Assistance in Think-Pair-Share Strategy on Students’ Learning Outcomes and Motivation - Suhaili, Ahmad; Budiasih, Endang; Wonorahardjo, Surjani (JPP (Jurnal Pendidikan dan Pembelajaran), 2020)
Abstract: The purpose of this study was to determine the effect of Learning Management System (LMS) assistance in Think-Pair-Share (TPS) strategy and the effect of Think-Pair-Share (TPS) strategy on students’ learning outcomes and motivation. Fourty students of two science classes were involved in this study. The treatment instruments used in this study were acid-base teaching materials, syllabus, student worksheets (LKPD), lesson plans (RPP), and Learning Management System (LMS). The measurement instrument employed a test question sheet and a student motivation questionnaire. The results showed differences in learning outcomes between students who are taught with the assistance of LMS in TPS strategy compared to students who are taught using TPS only are observed. There are differences in motivation among participants. Students who are taught with the assistance of LMS in TPS strategy compared to students who are taught with TPS strategy only.